MENINGKATKAN HASIL BELAJAR IPS SISWA MELALUI PENERAPAN METODE DISCOVERY LEARNING - Melda Kusumajaya Sinaga; Corry Corry; Anggiat Sinurat (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2023)
Social science learning is not only carried out with the aim that students have the social knowledge needed in social life, but also so that students have social skills and thinking skills in solving problems in society. The goal in this research is to improve students' social science learning outcomes through the application of the discovery learning method. The method used in this study was classroom action research conducted in class VI students at SD Negeri 8 Ronggurnihuta. The subjects in this study were 10 students who were selected by purposive random sampling method. The instruments used are observation sheets of learning activities and learning achievement tests. The results showed that there was an increase in student learning outcomes after improving the learning process in cycle II, with a completeness percentage of 90% which was only 50% previously. Moreover, when viewed from the average value of the class which in cycle I was only 64.0 increased to 82.0 in cycle II.